Low-tech MALL for EFL intensive class among university students in remote areas - Hasanah, Shofiyatul; Pradipta, Parahita (Universitas Muhammadiyah Sidoarjo, 2021)
Covid-19 pandemic situation has forced EFL teachers and students to create innovation in online classroom activities. Through a case study at one of private universities in Indonesia, this research aim at exploring the implementation of mobile phone used in learning process in low tech Mobile Assisted Language Learning (MALL). The data were collected from observation, in-depth interview, and document review. The findings reveal that mobile phone has an imperative role in concocting student to be full-fledge community, stimulating the feeling of perception, unexceptional mindfulness and teaching of socio-political and social classification. Further, mobile phone and its supporting materials in students’ tools rely upon whether there is appropriate security to keep the device, stockpiling of internet data package, wellsprings of electric supply, gracefully of each provider signal, availability to flexibility access in various areas, especially mountainous to remote area. Regarding the challenges, the students experienced multi-layer intricacies: (a) learning facilities including absence of speed data transfer capacity, (b) students’ awareness and proficiency in English, and (c) techno pedagogical insight over lecturers. This study implies that enhancement on the student capacity at low tech level of learning through mobile phone provide meaningful learning assistance, particularly in term of efficiency during classroom activities